2015
DOI: 10.1101/cshperspect.a017749
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Evidence of Genital Coevolution: The Roles of Natural Selection, Mate Choice, and Sexual Conflict

Abstract: Genital coevolution between the sexes is expected to be common because of the direct interaction between male and female genitalia during copulation. Here we review the diverse mechanisms of genital coevolution that include natural selection, female mate choice, male -male competition, and how their interactions generate sexual conflict that can lead to sexually antagonistic coevolution. Natural selection on genital morphology will result in size coevolution to allow for copulation to be mechanically possible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
150
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 98 publications
(139 reference statements)
3
150
0
Order By: Relevance
“…Such coevolutionary patterns could also result from the lock and key mechanism, male-male competition, or female choice, or a combination of them [91]. Thus, our discussion of the evidence in support of sexual conflict in spiders does not imply the absence of other mechanisms related to sexual selection.…”
Section: Discussionmentioning
confidence: 98%
“…Such coevolutionary patterns could also result from the lock and key mechanism, male-male competition, or female choice, or a combination of them [91]. Thus, our discussion of the evidence in support of sexual conflict in spiders does not imply the absence of other mechanisms related to sexual selection.…”
Section: Discussionmentioning
confidence: 98%
“…Secure attachment will prevent females from ending copulation as evidenced by cases in which male parts, or whole males, remain stuck in the female genital opening after they have been attacked and even died (Knoflach and van Harten 2001;Schneider et al 2001;Foellmer and Fairbairn 2003). Spider species vary widely in their genital morphology and genital coupling mechanisms (Eberhard 2004a), and firmness of the genital coupling may be a result of a sexual conflict over copulation duration in concert with sexual selection and natural selection (see Brennan and Prum 2014).…”
Section: Female Counterstrategies In Monogynous or Bigynous Matings Smentioning
confidence: 99%
“…Furthermore, Orbach et al's findings are novel and compelling DIGEST enough to provide more weight to the point of view that, even among closely related species, the rapid divergent evolution of genital shape in female cetaceans is facilitated by sexual selection pressures, just as Brennan and Prum (2015) described.…”
mentioning
confidence: 99%
“…In contrast, female genitalia are not as well studied, as they are generally thought to be relatively invariant (Ah-King et al 2014). However, it has been shown that the coevolution between male and female genitalia is expected to result from close mechanical interactions during the copulating process (Simmons and Garcia-Gonzalez 2011 adaptations, it is still very important to identify this pattern and confirm the potential evolutionary drivers of genital variation (Brennan and Prum 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation